STRATEGI GURU SEJARAH KEBUDAYAAN ISLAM DALAM MEREKONSTRUKSI MATERI TENTANG PEPERANGAN DALAM PERADABAN ISLAM DI MA ALI MAKSUM KRAPYAK YOGYAKARTA - Bisri, Khasan (Jurnal Pendidikan Agama Islam, 2016)
In the writing of Islamic cultural history, there are almost all the books write about war. The lesson books of Islamic cultural history in the school also not inseparable from material about war. This matter if not addressed properly by the teachers and students there was great potential false perception even erroneous, so there needs the right strategy for the students so that has not wrong perception about war in Islam. This research has purposes for knowing Islamic cultural history teacher strategy in reconstruction the material about war and its impact to the students. Data collection was done by interview, observation, documentation, and checking data validation with triangulation. The teacher method to reconstruct war material in Islamic civilization by explaining to the students the jihad and dakwah concept firstly, then the background of war happening, value / ibrah / moral value that can be taken from the war occurrence, and also explains various phenomenon or actual issues that was happening recently, and then connected with that war material. The impact for the students is when the teacher conveys the war material attractively and fun can be divided into two, cognitive impact and attitude impact. Keywords : Islamic Cultural History Strategy, Material Construction, War.